2013
DOI: 10.1002/jmv.23756
|View full text |Cite
|
Sign up to set email alerts
|

Influenza C virus infection in military recruits—symptoms and clinical manifestation

Abstract: Due to the lack of rapid diagnostic tests, clinical features of Influenza C virus infections are poorly characterized. Respiratory infections in military recruits in eastern Finland were monitored between July 2004 and December 2005 in order to study the epidemiology and clinical picture of infections caused by this virus. Blood samples were obtained at entry and at the end of the military service, and during each episode of respiratory infection to measure antibody responses against 10 viral and 2 bacterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
3
35
0
1
Order By: Relevance
“…While not extremely severe, these recruits suffered from illnesses serious enough to seek medical attention which resulted in the loss of man hours, something which cannot be afforded in a military setting. It was also recently reported by Kauppila et al 13. that FLUCV is an important respiratory tract infection amongst army conscripts in Finland.…”
Section: Discussionsupporting
confidence: 63%
“…While not extremely severe, these recruits suffered from illnesses serious enough to seek medical attention which resulted in the loss of man hours, something which cannot be afforded in a military setting. It was also recently reported by Kauppila et al 13. that FLUCV is an important respiratory tract infection amongst army conscripts in Finland.…”
Section: Discussionsupporting
confidence: 63%
“…Low rates were reported in a retrospective study Scottish study that screened 3300 respiratory samples collected from children and adults during the period from August 2006 to June 2008 with only six positive influenza C‐positive samples (0.2%) identified (with 4/6 from children ≤2 year) compared to 3.2% influenza A detections and 0.9% influenza B detections . Higher rates of influenza C infection have been reported in a Nigerian study, where 4.8% of the respiratory samples from children were positive for influenza C and Finnish study among young adult male military recruits, in which influenza C was identified in 4.2% of all samples. Influenza C can also be identified in a significant proportion of children hospitalized with lower respiratory tract infections, as reported by Shimizu et al .…”
Section: Introductionmentioning
confidence: 92%
“…Seroepidemiological studies have revealed that influenza C virus is widely distributed throughout the world (2)(3)(4)(5)(6), and recurrent infection with this virus occurs frequently in children and adults (7). However, the virus has been isolated by cell culture only occasionally, and long-term monitoring of influenza C viruses is rarely conducted.…”
mentioning
confidence: 99%
“…The monitoring of influenza C virus among children in the Yamagata and Miyagi Prefectures in Japan since 1988 has revealed that outbreaks of influenza C virus occur in winter or early summer at 1-or 2-year intervals (8)(9)(10). Influenza C virus infections, detected using molecular detection methods, have recently been reported in several countries, including Spain, France, Cuba, Canada, Italy, India, and Finland (7,(11)(12)(13)(14)(15)(16). A serological study conducted in the Philippines in 1984 indicated the existence of influenza C viruses, but the viruses themselves were not detected.…”
mentioning
confidence: 99%